2021
DOI: 10.1111/jocd.14434
|View full text |Cite
|
Sign up to set email alerts
|

Association between angiotensin‐converting enzyme gene insertion deletion polymorphism and androgenetic alopecia susceptibility among Egyptian patients: A preliminary case‐controlled study

Abstract: Background Androgenetic alopecia (AGA) is a prevalent condition with a complex etiopathogenesis. Angiotensin‐converting enzyme (ACE) gene located on the chromosome 17q23 contains an insertion (I) and deletion (D) polymorphism in the intron 16. This gene polymorphism plays a role in multiple inflammatory disorders. However, there are no studies investigating its association with AGA susceptibility. Objectives In this work, we aimed at exploring the association of ACE gene I/D polymorphism in AGA susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Lipoproteins have been found to play a direct role in preventing fungal infections along with infections caused by other microorganisms (Han, 2010). The APOE gene codes for the Apolipoprotein E. It is located on chromosome 19 and has three polymorphisms namely, 2, 3, and 4 (Mustafa et al 2023). These polymorphisms arise due to variation of C or T nucleotide at codons 112 and 158.…”
Section: Apoe Gene Polymorphism Status and Effect On Immunity Against...mentioning
confidence: 99%
See 3 more Smart Citations
“…Lipoproteins have been found to play a direct role in preventing fungal infections along with infections caused by other microorganisms (Han, 2010). The APOE gene codes for the Apolipoprotein E. It is located on chromosome 19 and has three polymorphisms namely, 2, 3, and 4 (Mustafa et al 2023). These polymorphisms arise due to variation of C or T nucleotide at codons 112 and 158.…”
Section: Apoe Gene Polymorphism Status and Effect On Immunity Against...mentioning
confidence: 99%
“…The six genotypes are created by different combinations such as (2/2, 3/3, 4/ 4, 2/3, 2/4, and 3/4) (Hatters et al 2009). This difference in status of APOE gene polymorphism affects the susceptibility to different diseases (Karpouzis, 2009) including superficial fungal infections (Mustafa et al 2023). Since APOE functions both as an immunomodulator as well as antimicrobial agent, identifying the status of APOE polymorphism in patients with superficial mycoses is an advantageous option (Tursen et al 2004).…”
Section: Apoe Gene Polymorphism Status and Effect On Immunity Against...mentioning
confidence: 99%
See 2 more Smart Citations
“…The I/D polymorphism of the ACE gene is due to an insertion (I) or deletion (D) of a 287-base pair (bp) Alu sequence in intron 16, giving rise to three genotypes: II, ID, and DD. 8 Previous research has indicated that the ACE DD genotype is linked with higher plasma ACE concentrations and increased vasoconstriction, which raises the risk of HTN-related IHD complications. However, this is controversial, as researchers have produced contradictory findings with no link between the DD genotype and IHD.…”
Section: Introductionmentioning
confidence: 99%